Sistem Deteksi Kematangan Cabai Hidroponik menggunakan Metode Thresholding pada Warna Hue, Saturation, dan Value - Cut Fahrani Dhania; Hurriyatul Fitriyah; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
In the agricultural industry, the main sector in the economic world, digital image processing is needed which aims to increase work productivity and time efficiency to choose the quality of crops to be marketed to the public due to lack of autonomy which results in high production costs and high work costs. Chili is the plant included Solanceae genus that can be implanted in a hydroponic planting system that makes water a substitute for soil media. This hydroponic chili plant uses the Dutch Bucket planting system because it can be used in narrow environments and can be used flexibly. This detection is assisted by a simulator robot that has been designed with a certain height and distance, namely a height of 20 cm and a distance of 30 cm and 20 cm with the help of a Lux Meter to measure the intensity of ambient light which is then designed using Qt Designer as a Graphical User Interface platform which will display the results of hydroponic chili detection through the bounding box. The accuracy value on the successful detection of hydroponic chili maturity resulted in a percentage of 93% and a computational mean value of 3.841 seconds.